World Class Operations in Aftermarket Logistics at Rolls Royce Group Plc - Vaithiyanathan, Shivany; Sbardello, Marco; Leung, Lily (2005)
Rolls Royce Group Plc (R-R) is transforming the way in which it operates in its aftermarket. The company is moving from a product based Time and Materials (T&M) business to a service based way of working which includes Total Care Agreements (TCA). Under T&M when an engine is repaired and overhauled customers are charged based upon cost plus margin, whereas under TCA the cost to the customer is fixed. The profitability of TCA depends on margin improvements through cost and risk reduction and operational improvements. This requires supply chain and logistics support. This project was undertaken to support the Aftermarket Logistics Operating Model (ALOM) to investigate the following six business policy options - Workscope Standardisation - Component Inspection Policy - Component Repair Vendor (CRV) smoothing - Kitting - Module Swapping - Aftermarket Service Centres (ASC)